Protective Immunity in Macaques Vaccinated with a Modified Vaccinia Virus Ankara-Based Measles Virus Vaccine in the Presence of Passively Acquired Antibodies - Stittelaar, Koert J. (American Society for Microbiology, 2000)
Recombinant modified vaccinia virus Ankara (MVA), encoding the measles virus (MV) fusion (F) and hemagglutinin (H) (MVA-FH) glycoproteins, was evaluated in an MV vaccination-challenge model with macaques. Animals were vaccinated twice in the absence or presence of passively transferred MV-neutralizing macaque antibodies and challenged 1 year later intratracheally with wild-type MV. After the second vaccination with MVA-FH, all the animals developed MV-neutralizing antibodies and MV-specific T-cell responses. Although MVA-FH was slightly less effective in inducing MV-neutralizing antibodies in the absence of passively transferred antibodies than the currently used live attenuated vaccine, it proved to be more effective in the presence of such antibodies. All vaccinated animals were effectively protected from the challenge infection. These data suggest that MVA-FH should be further tested as an alternative to the current vaccine for infants with maternally acquired MV-neutralizing antibodies and for adults with waning vaccine-induced immunity.